Experimental evidence that density mediates negative frequency‐dependent selection on aggression. (14th March 2018) - Kilgour, R. Julia; McAdam, Andrew G.; Betini, Gustavo S.; Norris, D. Ryan
Abstract: Aggression can be beneficial in competitive environments if aggressive individuals are more likely to access resources than non‐aggressive individuals. However, variation in aggressive behaviour persists within populations, suggesting that high levels of aggression might not always be favoured. The goal of this study was to experimentally assess the effects of population density and phenotypic frequency on selection on aggression in a competitive environment. We compared survival of two strains of Drosophila melanogaster that differ in aggression across three density treatments and five frequency treatments (single strain groups, equal numbers of each strain and strains mixed at 3:1 and 1:3 ratios) during a period of limited resources. While there was no difference in survival across single‐strain treatments, survival was strongly density dependent, with declining survival as density increased. Furthermore, at medium and high densities, there was evidence of negative frequency‐dependent selection, where rare strains experienced greater survival than common strains. However, there was no evidence of negative frequency‐dependent selection at low density. Our results indicate that the benefits of aggression during periods of limited resources can depend on the interaction between the phenotypic composition of populations and population density, both of which are mechanisms that could maintain variation in aggressive behaviours within natural populations. Abstract : This is the first study to experimentally demonstrate that alternative aggressive phenotypes can be maintained using negative frequency‐dependent selection. These results also show how the effect of NFDS is influenced by density.